Comparing the Irrigation Systems in Different Agro-Ecological Zone of Domar Upazila, Nilphamari, Bangladesh - Subaran Chandra Sarker; S. M. Zahid Hasan (International Research in Environment, Geography and Earth Science Vol. 8, 2021)
An Agro-ecological (AEZ) zone describes it’s all characteristics about those phenomena which are related with agriculture such as temperature, rainfall, humidity, soil quality, soil fertility, crop pattern of a specific region. This study was done to find out irrigation distribution, crop pattern, and a relation between them. 12 AEZ units divided in a study area on the basis of topography, soil characteristics and development possibility from H. Brammer’s research “Agroecological aspects on agricultural research of Bangladesh”. In this study, data were collected by questionnaire survey, official documents and irrigation machine’s locations data were collected by using Germin eTrex 30 GPS machine and Google Earth Pro. Irrigation distribution maps were created by inserting location data into XY data input on ArcGIS 10. Comparing satellite images of different time of a year from Google earth, Crop pattern map has produced. The result here shown in Domar upazila found 4242 irrigation machines including electric pump, diesel pump and deep tubewell and also found relation between irrigation systems and crop pattern. In findings, there mainly diesel pump used in AEZ unit 1, AEZ unit 5 and AEZ Unit 12 and these AEZ units are dominated by Potato, Maize, Groundnut, Chili and Tobacco cultivation and rest AEZ units are dominated by Boro cultivation where used deep tubewell and electric pump. By proper distribution of the irrigation machine may need less time to irrigate the same land that is irrigated by haphazardly distributed. This research helps to compare irrigation systems of different AEZ units and ensure the proper irrigation system. Proper distribution of irrigation systems according to AEZ units improve the agricultural production and also improve the socio-economic condition. In future, for further research related to this study a researcher will get help from this study to identified crop pattern distribution, irrigation machines distribution, relation with AEZ units, crop pattern and irrigation system and application of GIS.